Door to Door: Preventive Measures Against Fatigue Among Hauler Operators at PT Putra Perkasa Abadi’s MIPL Site - Fauzi Jatmiko; Ganda Sukma Nugraha; Ahkamil Hakim Fashli; Robby Maulana; Fika Kurniawan (Journal of Social Research, 2026)
Fatigue or work fatigue is one of the main causes of work accidents in hauler operators in the mining sector. In the June-September 2024 period, PT Putra Perkasa Abadi (PPA) Jobsite MIPL recorded 10 incidents, with 5 cases caused by operator fatigue. The analysis showed operators remained working in fatigued conditions and were reluctant to report the condition. Even though the Driving Monitoring System (DMS) has been used, psychological factors and lack of family support have made fatigue control not optimal. This study aims to evaluate the effectiveness of the Door to Door (DtD) approach based on Family Support Safety in reducing incidents due to fatigue in hauler operators. Uses the Quality Control Project (QCP) approach through the Door to Door (DtD) program, which is a direct visit to the operator: P's family home with the highest DMS findings. The program was implemented in October–November 2024 by a cross-departmental team (SHE, Production, and HCGA). The implementation of the program showed a decrease in incidents due to fatigue from 5 cases to 0 cases, as well as a 100% reduction in the company's potential losses from Rp69,907,004 to Rp0. Family Support Safety through Door to Door (DtD) has proven to be effective as a preventive strategy in managing hauler operator fatigue and can strengthen the occupational safety system in the mining sector.